PENGEMBANGAN MODEL MANAJEMEN BERBASIS SEKOLAH BERORIENTASI LITERASI NUMERASI DI SD NEGERI 1 WEDA - Wachyudi Eksan; Usman Amiruddin; Masrifa Umasugi (Jurnal Pendidikan dan Ekonomi (JUPEK), 2026)
This study aimed to develop a School-Based Management (SBM) Model Oriented toward Numeracy Literacy as a guideline for managing literacy and numeracy programs at SD Negeri 1 Weda. The study employed a Research and Development (R&D) approach using the ADDIE model, which consists of the analysis, design, development, implementation, and evaluation stages. Data were collected through observations, interviews, questionnaires, document analysis, and expert validation, and were analyzed using descriptive qualitative and quantitative techniques. The needs analysis revealed that although the implementation of School-Based Management had been relatively effective, numeracy literacy programs had not been fully integrated into the school's management functions. The main issues identified included the absence of numeracy literacy programs in the School Activity and Budget Plan (RKAS), the lack of a School Numeracy Literacy Team, incidental program implementation, the absence of a monitoring and evaluation system based on numeracy literacy indicators, and limited parental involvement. Based on these findings, an SBM-oriented Numeracy Literacy Model was developed, comprising five main components: planning, organizing, implementation, monitoring, and evaluation. Expert validation and limited field testing indicated that the model is valid, systematic, practical, and applicable. The model enhances the integration of numeracy literacy program management, strengthens collaboration among school stakeholders, and supports the establishment of a sustainable literacy and numeracy culture. Therefore, the model is considered feasible as a guideline for managing numeracy literacy programs in primary schools to improve both learning quality and school governance.